Roman law before the twelve tables : an interdisciplinary approach - Bell, Sinclair; Bell, Sinclair; Du Plessis, Paul J.; Du Plessis, Paul J. (Edinburgh University Press, 2020)
Intro -- The Contributors -- Introduction: The Dawn of Roman Law -- Part I The Materiality of Roman Law: New Archaeological Discoveries -- 1. Roman Law in its Italic Context -- 2. Central Italian Elite Groups as Aristocratic Houses in the Ninth to Sixth Centuries BCE -- 3. Authority and Display in Sixth-Century Etruria: The Vicchio Stele -- Part II Constructing Early Roman Law: Sources and Methods -- 4. The Twelve Tables and the leges regiae: A Problem of Validity -- 5. The leges regiae in Livy: Narratological and Stylistic Strategies -- 6. The leges regiae through Tradition, Historicity and Invention: A Comparison of Historico-literary and Jurisprudential Sources -- 7. The Laws of the Kings - A View from a Distance -- 8. Beyond the Pomerium: Expansion and Legislative Authority in Archaic Rome -- Part III Roman Law in Historiography and Theory -- 9. Niebuhr and Bachofen: New Forms of Evidence on Roman History -- 10. Finding Melanesia in Ancient Rome: Mauss' Anthropology of nexum -- Index.